HIS Implementation in Small Hospital - Resia Perwirani (Minat Sistem Informasi Manajemen Kesehatan Fakultas Kedokteran UGM, 2022)
Background: Budi Rahayu Hospital at Magelang City has implemented HIS in partnership with the SIMKES FKKMK laboratory of Gadjah Mada University since April 2021. During the initial four months of implementation, Budi Rahayu Hospital experienced various challenges. For understanding and overcome the challenges, it is necessary to construct a strategy of HIS implementation, and then offer a proper recommendation based on study.Methods: This study is a descriptive qualitative with action research design that describe four stages of action research i.e Diagnosing, Planning, Action, and Evaluation. On the Diagnosing stage, Author arrange an interview and discussion with Hospital Team. Next, Author plan a strategy to generate suitable recommendations for the successful implementation of HIS. In the Action stage, author conduct an implementation review and assistance. Author also manage an UAT as a evaluation stage distributed to respondents using a questionnaire. The study is performed by observing of HIS implementation from September – December 2021. The subject of this study is chosen purposively from departments involved, with total 20 end-users respondents on multiple service units to capture data in a real environtment when HIS is used for healthcare services to patients.Results: Strategic actions for smooth implementation is active involvements and collaboration from developer team and hospital team monitored by regional health services. the hospital team and developer team formed an online communication group as a place to discuss the problems encountered. There are monitoring activities that involved by regional health services, so the timeline that has been set runs according to the target and the hospital gets optimal benefits of HIS implementation. System acceptance is important for the further development of HIS. The score of HIS acceptance at Budi Rahayu Hospital is 70% based on 85% scenario that execute successfully. Based on system performance, continues maintenance and communication among implementation team, HIS can be accepted with condition of continuous improvement and adjustment.Conclusions: Active involvements and collaboration from developer team and hospital team, performance improvement and availability of the system is very crucial for user acceptance, satisfaction and overall success of HIS implementation. Keywords: HIS, Implementation, UAT